Development Of Multicultural-Based Islamic Educational Institutions In Realizing Peaceful Life In Pesantren - Mistria Harmonis; Masykuri Bakri (Institut Agama Islam An-Nawawi Purworejo, 2023)
This study aims to develop multicultural Islamic educational institutions that focus on several aspects of the study to realize peaceful life in the Nurul Jadid Paiton Islamic boarding school, Probolinggo. In order to obtain data from research results, research was carried out with a qualitative approach and a case study type. The data collection technique uses the snowball sampling technique. The data sources used are primary and secondary. Data collection techniques used participant observation, in-depth interviews and documentation. Meanwhile, data analysis techniques used the Miles Huberman model, which included data reduction, data display and concluding. The results of this study indicate that the development of multicultural Islamic education institutions in realizing peaceful attitudes at the Nurul Jadid Paiton Islamic Boarding School in Probolinggo is: Strengthening the Multicultural-based Islamic Education Institution System in Islamic Boarding Schools, Integrating Multicultural Islamic educational values in the Education System in Islamic Boarding Schools, Planning a multicultural-based curriculum in Islamic Boarding School Islamic Education institutions Management of multicultural-based learning in Islamic Boarding School educational institutions, Multicultural-based HR Management of Educators and Education Personnel in Islamic Boarding Schools.